Level of the proliferative activity of lymphocytes in case of mycosis fungoides and plaque parapsoriasis - A. S. Zhukov; I. E. Belousova; V. R. Khairutdinov; I. N. Telichko; A. V. Samtsov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The level of the proliferative activity is an important predictor of a number of oncologic diseases; at the same time, its diagnostic value for mycosis fungoides was not adequately investigated. Goal. To study the proliferative activity of lymphocytes in the skin of patients suffering form mycosis fungoides and plaque parapsoriasis. Materials and methods. The level of CD3+ and Ki-67+ cells was determined in skin biopsy samples taken from patients suffering from mycosis fungoides (18 subjects) and plaque parapsoriasis (6 subjects) by means of immunohistochemistry. The epidermal to dermal skin cell proliferative activity ratio (Ki-67+) and cell proliferative activity index were calculated. The control group comprised 16 healthy people. Results. The epidermal to dermal skin cell proliferative activity ratio amounted to 10.9 in healthy people, 5.43 in patients suffering from plaque parapsoriasis, and 3.84 and 2.42 in patients suffering from mycosis fungoides, spotty and plaque and tumor stages, respectively. The percentage of proliferative CD3+Ki-67+ cells relative to the total number of T-lymphocytes amounted to 1% in the patients suffering from plaque parapsoriasis and 3% in the patients with mycosis fungoides, spotty stage. Conclusion. The epidermal to dermal skin cell proliferative activity ratio (Ki-67+) in patients suffering from mycosis fungoides at any stage is lower than that in healthy subjects and patients suffering from parapsoriasis. The cell proliferative activity index was higher in the patients with mycosis fungoides, plaque and tumor stage, than in the patients with parapsoriasis. The number of CD3+Ki-67+ cells was higher in the patients with mycosis fungoides, spotty and plaque and tumor stages, than in the healthy subjects and patients suffering from parapsoriasis.